The perception of nursing leaders towards communication and relationship management competencies in using digital platforms during COVID‐19 in Qatar: A cross‐sectional study - Laith F. Daradkeh (14779558) (2023)
Aim To evaluate nursing leaders' perception of communication and relationship management competencies while using digital platforms during the COVID-19 pandemic. Background Nursing leaders can achieve effective leadership by mastering these competencies leading to an overall improvement in the quality of nursing care. The COVID-19 pandemic has brought numerous challenges in communication, and digital platforms have been widely used in healthcare settings to mitigate contagion. Design Cross-sectional. Methods The study was conducted between February and March 2021. A survey was adopted from the American Organization of Nurse Executives (AONE) and was sent to nursing leaders in Qatar through email. Results A total of 250 nurse leaders were invited to participate, but only 116 responded (RR 46.4%). The male participants represented a more significant proportion of 64.10%. Influencing behaviour, relationship management and effective communication had the lowest scores, which indicates low competency. Conclusions Despite obtaining satisfying scores, nursing leaders in Qatar should strive for professional development and knowledge acquisition to improve their communications and relationship management competencies. Implications for Nursing Management Healthcare organizations must understand that nursing leaders should strive for professional development and knowledge acquisition to improve their communication and management. Other Information Published in: Journal of Nursing Management License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1111/jonm.13722